Adsorption of copper from aqueous solution onto agricultural Adsorbents: Kinetics and isotherm studies. (2020) - Bashir, Misbah; Tyagi, Shivani; Annachhatre, Ajit P.
Highlights: Copper adsorption onto egg shell, spent tea leaves and their biochar was studied. Copper removal of 85–90% and adsorption capacity of 420–450 mg/g was observed. Freundlich isotherm model fitted the best for both the adsorbents. Egg shell followed pseudo-first-order adsorption kinetics. Spent tea leaves followed pseudo-second-order adsorption kinetics. Abstract: Investigations were conducted to evaluate the adsorption of copper ions from artificially stimulated wastewater onto Egg Shells (ES), Spent Tea Leaves (STL) and their biochars. Batch studies on ES and STL were carried out at varying pH (3–8), contact time (30–150 min), solid:liquid ratio (0.25:25–2:25) and initial copper concentration (5–20 ppm). On the other hand, batch studies with biochar as adsorbent were conducted at contact time of 180 min, pH 6, solid:liquid ratio of 1:50 and 20 ppm of initial copper concentration. Kinetics and isotherm studies were taken place for evaluating the potential of ES and STL for adsorption of copper ions from artificially stimulated wastewater. Copper removal by ES and STL was 84.5% (adsorption capacity 422.5 mg/g) and 91% (adsorption capacity 447.5 mg/g) under the optimum conditions respectively. EDX-SEM analysis of ES and STL indicated that the particles were present on ES as well as STL after adsorption process. Elemental analysis showed 1.26% and 0.89% by weight were present due to copper adsorption onto ES and STL respectively. STL biochar yielded the best adsorption amongst all with more than 99% of copper removal. Its EDX-SEM analysis showed that there was the presence of particles at the surface of STL biocahr after adsorption process having 0.59% weight due to copper adsorption. Adsorption isotherm studies on ES and STL revealed multilayer adsorption with Freundlich isotherm. Study on adsorption kinetics for ES and STL revealed that ES followed pseudo-first-order kinetics while as STL followed pseudo-second-order kinetics.